RELEVANCE OF FIBONACCI SEQUENCE IN BIOLOGY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The Fibonacci sequence, with its intriguing pattern of numbers (1, 1, 2, 3, 5, 8, 13...), extends beyond the realm of mathematics and finds surprising relevance in the world of biology. This article explores the compelling evidence of the Fibonacci sequence's presence in various biological phenomena, highlighting its role in shaping the natural world.